2009
DOI: 10.1016/j.comgeo.2008.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Towards a definition of higher order constrained Delaunay triangulations

Abstract: When a triangulation of a set of points and edges is required, the constrained Delaunay triangulation is often the preferred choice because of its well-shaped triangles. However, in applications like terrain modeling, it is sometimes necessary to have flexibility to optimize some other aspect of the triangulation, while still having nicely-shaped triangles and including a set of constraints. Higher order Delaunay triangulations were introduced to provide a class of well-shaped triangulations, flexible enough t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The algorithms presented in this paper are general, in the sense that they were designed to be able to work for a large number of measures. Even though any of the definitions proposed in [22] can easily be plugged in into the algorithms, many of the improvements on the running time achieved here would be lost. It may be interesting to try to adapt the polygon triangulation algorithms to some of the definitions proposed in [22].…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…The algorithms presented in this paper are general, in the sense that they were designed to be able to work for a large number of measures. Even though any of the definitions proposed in [22] can easily be plugged in into the algorithms, many of the improvements on the running time achieved here would be lost. It may be interesting to try to adapt the polygon triangulation algorithms to some of the definitions proposed in [22].…”
Section: Discussionmentioning
confidence: 92%
“…As mentioned in the introduction, there seems to be no single definition of the constrained order of a triangle that generalizes the concept of constrained Delaunay triangulation to higher orders in a completely natural way. The authors concluded in [22] that the choice of such a definition will depend on the application in mind. The algorithms presented in this paper are general, in the sense that they were designed to be able to work for a large number of measures.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In this chapter we study the flip graph of higher order Delaunay triangulations. Most previous work on such triangulations focused on algorithmic questions related to finding order-k triangulations that are optimal with respect to extra criteria [104,97,98], or on evaluating their effectiveness in practical settings [20,45]. One of the few theoretical aspects studied is the asymptotic number of order-k triangulations [82].…”
Section: Higher Order Delaunay Triangulations and Flipsmentioning
confidence: 99%